Partial Edentulousness in Patients Visiting the Dental Out-Patient Department of Gandaki Medical College, Pokhara, Nepal - A. Bhandari; A. Manandhar; P. Manandhar (Journal of Gandaki Medical College, 2019)
Introduction: Partial edentulousness is a dental arch in which one or more but not all natural teeth are missing due to dental caries, periodontal problems, trauma etc. It causes difficulty in chewing food, alteration of speech and unpleasant esthetics which adversely affect the general health and quality of life.